MENGUKUR KEPUASAN PELANGGAN BERDASARKAN KELUHAN DAN SARAN PELANGGAN MENGGUNAKAN ALGORITMA C4.5 - Putra, Toni Wijanarko Adi; Patria, Daffa Wahyu; Hartono, Budi; Jamaludin, Haris (UNIVERSITAS STEKOM, 2024)
The influence of service quality on customer satisfaction is very large. Criticism and suggestions from customers are a must for researchers because they can measure customer satisfaction. The higher the positive response and rating, the ideally it is a sign that customers are satisfied with the service they receive. Quantitative research methods are defined as part of a series of systematic investigations of phenomena by collecting data to then be measured using mathematical or computational statistical techniques. Meanwhile, quantitative relies on questionnaires as a technique for obtaining research data. The questionnaire will be distributed by the researcher to a group of people who are considered capable of representing the problem and can answer the research questions. 1. With the large number of patients undergoing examinations at the Ngaliyan Community Health Center, it is necessary to add more seating to the waiting room so that patients can be more comfortable. 2. Arrange the registration waiting room and medicine collection waiting room so that they can be separated. In the long term, additional space is needed. 3. It is necessary to improve the service process for patients so that the process is faster and more timely.